The Short-Run Impact of Indonesia's Large-Scale Social Restriction on Intra-Generational Household Economic Mobility - Samuda, Sri Juli Asdiyanti; Nasrudin, Rus'an (Universitas Airlangga, 2023)
This study aims to estimate the impact of policy responses due to the Covid-19 pandemic on intra-generational household economic mobility in Indonesia. Given the many policy interventions during the Covid-19 pandemic in 2020, this study focuses on the implementation of partial lockdowns known as PSBB policy in four districts (Bogor Regency, Bekasi Regency, Bogor City, and Bekasi City). In order to have a causal relationship, this study performs Synthetic Control Method to construct hypothetical counterfactual regions for districts that implement PSBB policy. Based on multinomial logit estimations, this study found that the implementation of PSBB adversely affects household economic mobility in rural districts but does not significantly affect household economic mobility in urban districts in the short run.